Electrochemical behavior of CuO/rGO nanopellets for flexible supercapacitor, non-enzymatic glucose, and H2O2 sensing application. Issue 12 (15th June 2021) - Lohar, G.M.; Pore, O.C.; Fulari, A.V.
Abstract: In the present article, graphene oxide (GO) sheets and monoclinic copper oxide (CuO) nanocrystals are connected with each other and result in the formation of CuO/rGO nanopellets, and these nanopellets synthesized using coprecipitation method. The nanopellet structured CuO/rGO composite on carbon cloth, which act as current collector exhibits specific capacitance of 188 F g −1 at a current density of 0.2 A g −1 and up to 96.3% capacity retention after 2000 charge-discharge cycles. It shows a maximum energy density of 7.32 Wh kg −1 and power density of 53 W kg −1 . The glucose sensing characteristics of CuO/rGO nanopellet is investigated on carbon cloth and ITO substrate. It shows glucose sensitivity of 0.805 mA mM −1 cm −2 and 0.2982 mA mM −1 cm −2 for a bundle like structured CuO/rGO composite on carbon cloth and ITO substrate, respectively. Further H2 O2 sensing is studied on ITO substrate, which manifests H2 O2 sensitivity of 84.39 μA mM −1 cm −2 . The results indicate that nanopellet structured CuO/rGO composite could be a promising electrode material for supercapacitor, glucose, and H2 O2 sensor.